(untitled) (Conferencea, 2023)
One of the main challenges for business companies today is the crises that arise in the virtual world. Managing them is difficult even in the context of digital communication, since the unlimited resources of the online space give rise to new challenges and create previously unknown mechanisms for responding to them. Crises, on the one hand, are characterized by negative consequences (or the possibility of negative consequences), stress, emotional damage, traumatic impact (Freberg, 2011. 8), although it is also obvious that a crisis can generatechanges in events. for the better. And this depends on crisis preparation,mitigation and crisis communication strategies.